2017
DOI: 10.1002/adma.201700412
|View full text |Cite
|
Sign up to set email alerts
|

Origami‐Based Reconfigurable Metamaterials for Tunable Chirality

Abstract: Origami is the art of folding two-dimensional (2D) materials, such as a flat sheet of paper, into complex and elaborate three-dimensional (3D) objects. This study reports origami-based metamaterials whose electromagnetic responses are dynamically controllable via switching the folding state of Miura-ori split-ring resonators. The deformation of the Miura-ori unit along the third dimension induces net electric and magnetic dipoles of split-ring resonators parallel or anti-parallel to each other, leading to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
138
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(149 citation statements)
references
References 51 publications
0
138
0
Order By: Relevance
“…Meanwhile, two reversed resonances appear in the CD spectra of the folded metamaterial, which clearly manifests that the folded metamaterial exhibits the distinct chirality characteristics at multiband. It is shown that the CD magnitude of folded metamaterial becomes minimum and reaches down to −0.64 at the first chiral response, while a much larger CD as high as 0.8 at 72.8 THz is experimentally achieved for the second chiral response, which is unprecedentedly high for a single layer metasurface without diffraction . This indicates that the folded metamaterial significantly breaks the spin degeneracy of incident light and achieves high‐efficient spin‐selective transmission.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Meanwhile, two reversed resonances appear in the CD spectra of the folded metamaterial, which clearly manifests that the folded metamaterial exhibits the distinct chirality characteristics at multiband. It is shown that the CD magnitude of folded metamaterial becomes minimum and reaches down to −0.64 at the first chiral response, while a much larger CD as high as 0.8 at 72.8 THz is experimentally achieved for the second chiral response, which is unprecedentedly high for a single layer metasurface without diffraction . This indicates that the folded metamaterial significantly breaks the spin degeneracy of incident light and achieves high‐efficient spin‐selective transmission.…”
mentioning
confidence: 96%
“…Recently, the concept of origami or kirigami provides alternative approach to construct 3D structures. Mechanically tunable chirality switching has been implemented by origami metamaterials at microwave regime . Spin‐selective transmission has been demonstrated by chiral folded antisymmetric split‐ring resonators (SRRs) at infrared region .…”
mentioning
confidence: 99%
“…[38,39] Origami/kirigami, the ancient art of folding a sheet of paper into 3D decorative shapes, is not only an inspiring technique to create sophisticated shapes but also a surprisingly versatile platform to investigate a host of shape changing metadevices with customized functionalities. [38,39] Origami/kirigami, the ancient art of folding a sheet of paper into 3D decorative shapes, is not only an inspiring technique to create sophisticated shapes but also a surprisingly versatile platform to investigate a host of shape changing metadevices with customized functionalities.…”
mentioning
confidence: 99%
“…In addition, the configurations in these solutions are not reconfigurable and the metamaterials lack the flexibility to adapt themselves to changed working conditions. Tunability of 3D cubic nanostructures can be achieved by imposing external stimulus such as strain, temperature, and load . Of these structures, the metal components can be deformed in response to the stretching and folding of the substrates which are specifically designed in a sandwich‐like composite or a Miura‐origami pattern .…”
mentioning
confidence: 99%
“…Tunability of 3D cubic nanostructures can be achieved by imposing external stimulus such as strain, temperature, and load . Of these structures, the metal components can be deformed in response to the stretching and folding of the substrates which are specifically designed in a sandwich‐like composite or a Miura‐origami pattern . Based on the concept of compressive buckling, the geometry of metal pattern bonded at some specified regions to the substrate can be transformed from a planar sheet to some complex 3D architectures like cuboid cages, flowers and scaffolds when the elongated elastomeric substrate retracts .…”
mentioning
confidence: 99%